2005
DOI: 10.1115/1.2133764
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Response of Bovine Articular Cartilage Under Creep Loading Following Proteoglycan Digestion With Chondroitinase ABC

Abstract: SummaryThe specific aim of this study was to investigate the effect of chondroitinase ABC treatment on the frictional response of bovine articular cartilage against glass, under creep loading. The hypothesis is that chondroitinase ABC treatment increases the friction coefficient of bovine articular cartilage under creep. Articular cartilage samples (n=12) harvested from two bovine knee joints (1-3 monthsold) were divided into a control group (intact specimens) and a treated group (chondroitinase ABC digestion)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 32 publications
6
46
2
3
Order By: Relevance
“…The friction measurements (cartilage-on-glass) were performed in unconfined compression creep, under reciprocal sliding motion consisting of 100 cycles over a range of ±4.5mm, at 1 mm/s. Under this testing configuration, the friction coefficient rises monotonically over time, from a minimum value denoted by μ min to a steady-state equilibrium value denoted by μ eq , as shown in previous studies (Krishnan et al 2004; Basalo et al 2006). The pausing interval between two consecutive sliding cycles was gradually increased as the friction coefficient increased.…”
Section: Methodssupporting
confidence: 73%
See 2 more Smart Citations
“…The friction measurements (cartilage-on-glass) were performed in unconfined compression creep, under reciprocal sliding motion consisting of 100 cycles over a range of ±4.5mm, at 1 mm/s. Under this testing configuration, the friction coefficient rises monotonically over time, from a minimum value denoted by μ min to a steady-state equilibrium value denoted by μ eq , as shown in previous studies (Krishnan et al 2004; Basalo et al 2006). The pausing interval between two consecutive sliding cycles was gradually increased as the friction coefficient increased.…”
Section: Methodssupporting
confidence: 73%
“…First, it was shown that cartilage that was enzymatically degraded with chondroitinase ABC exhibits a significantly higher friction coefficient than normal tissue (Basalo et al 2005; Basalo et al 2006), complementing the findings of an earlier study(Kumar et al 2001); then it was shown that normal cartilage that had been incubated or tested in a saline bath with 100 mg/ml CS, exhibited much lower friction than tissue tested in saline with 10 mg/ml CS, or saline alone(Basalo et al 2007). …”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…A creep stress of 0.78 MPa was selected to mimic the contact stresses experienced in the knee during jogging, 42 and effective perimeter velocity of 22 mm s −1 was selected to mimic the upper physiologic range of daily femoral-tibial sliding velocities. 43 This procedure yields COFs that increase as a function of time 44 as shown in Figure 2, with COFs equilibrating concurrent with creep deformation equilibrium. The differences in COF became statistically significant between 60 w/v% treated and non-treated tissue approximately half-way into the three-hour test (24% reduction in COF compared to non-treated tissue at the test’s completion), whereas the difference in COF between 20 w/v% and non-treated tissue demonstrated a non-statistically significant (p = 0.48) 5% reduction in COF compared to non-treated tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Prior in vitro and in vivo friction studies have induced degradation of bovine articular cartilage by enzymatic action [1, 2, 3, 4, 5] or by mechanical abrasion [6, 7] as a means to simulate osteoarthritis (OA), generally reporting that the friction coefficient increases with degradation. Gene knockout studies have examined the frictional response of animal joints lacking expression of lubricin/superficial zone protein by PRG4 [8, 9], also showing an increase in friction and wear.…”
Section: Introductionmentioning
confidence: 99%